Las formas de la verdad : investigación, docuficción y memoria en la novela hispánica (2000-2015) - Martínez Rubio, José, 1985- (Barcelona : Anthropos Editorial ; Ciudad de México, D.F : Universidad Autónoma Metropolitana, Unidad Iztapalapa, División de Ciencias Sociales y Humanidades, 2015)
This volume analyzes novels written in Spain and Latin America between 2000 and 2015. Apart from literature, psychoanalysis, philosophy, sociology, and cultural history, this text helps address phenomena such as docudrama, the cultural need for reality, and identity creation.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed February 27, 2017)
Keywords: Spanish fiction -- History and criticism -- 21st century; Latin American fiction -- History and criticism -- 21st century; Historical fiction, Spanish -- History and criticism; Historical fiction, Spanish American -- History and criticism; Literature and history -- Spain; Literature and history -- Latin America; Fiction -- Technique; History in literature; Biography in literature; Collective memory in literature; Research in literature; Electronic books